HEXANIC FRACTION OF TURMERIC POWDER ATTENUATES MURINE MODEL OF INDUCEDNOCICEPTION AND ITS POSSIBLE MECHANISMS OF ACTION - Suloon, Jacklin; Mohamad, Azam Shah; Ming-Tatt, Lee; Akhtar, Muhammad Nadeem; Perimal, Enoch Kumar; Akira, Ahmad; Israf, Daud Ahmad; Sulaiman, Mohd Roslan (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: The current study was conducted to further examine the antinociceptive activity of hexane fraction of turmeric powder (HFTP)and to elucidate the possible mechanisms of action underlying its antinociceptive activity in various experimental models of chemical- andthermal-induced nociception.Materials and Methods: Acetic acid-induced abdominal constriction, hot-plate, formalin-, capsaicin- and glutamate-induced paw licking testsin mice were employed in the antinociceptive investigation of HFTP. In all experiments, HFTP was administered intraperitoneally at the dosesof 0.1, 0.5, 1.0 and 5.0 mg/kg. In a separate group of experiments, the possible sedative and toxic effects of HFTP were tested in rota rod andpreliminary acute toxicity tests, respectively.Results: It was demonstrated that HFTP exerted significant dose-dependent antinociceptive responses in the acetic acid-induced abdominalconstriction, hot-plate, formalin-, capsaicin- and glutamate-induced paw licking tests. It was also demonstrated that pretreatment with naloxone,produced no significant effect on the antinociception induced by HFTP. Moreover, administration of HFTP shows no significant interference inlocomotor activity of the rota rod test, and in the preliminary acute toxicity test, neither abnormal behaviours nor mortality were observed.Conclusion: Together, these results indicated that HFTP-induced antinociceptive activity at doses devoid of any detectable toxicity and sedativeeffects exerts pronounced peripheral and central antinociceptive effects, with no involvement of opioidergic system but possibly related to itsability to interact with TRPV1 receptors and the glutamatergic system.